Venoarterial extracorporeal membrane oxygenation use in staged combined heart–kidney transplant - Al Saadi, Tareq (J Surg Case Rep, 2020)
Outside of heart and lung transplantation, only few cases have been reported describing venoarterial extracorporeal membrane oxygenation (VA-ECMO) use in solid organ transplantation. We present a case of a staged combined heart–kidney transplant in which VA-ECMO was utilized after a complicated orthotopic heart transplantation to successfully complete the subsequent renal transplantation.